AB0466 Safety of rituximab in patients with rheumatoid arthritis. eleven-year follow-up observational study. (12th June 2018) - Rodriguez García, S.D.L.C.; Castellanos-Moreira, R.; Hernandez-Miguel, M.V.; Cuervo, A.; Camacho, O.; Ruiz-Esquide, V.; Ramirez, J.; Cañete, J.D.; Gomez Puerta, J.; Sanmartí, R.
Abstract : Background: Rituximab (RTX) is a chimeric monoclonal antibody approved for the treatment of active rheumatoid arthritis (RA) in patients who failed to respond to tumour necrosis factor inhibitors (TNFi). Due to its effect on induction of B cell depletion, the administration of multiple cycles can lead to a decrease in immunoglobulins (Ig) which may increase the risk of infection. Objectives: To assess the long-term safety of RTX in patients with RA and to evaluate factors associated with the presence of infections. Methods: A retrospective observational study was conducted including patients with RA treated in a tertiary hospital between June 2006 and May 2017 who had received at least one RTX cycle. At RTX initiation we analysed: age, sex, comorbidities and Charlson score, disease duration, presence of rheumatoid factor (RF)/anti-citrullinated protein antibodies (ACPA), disease activity (DAS28), acute phase reactants (CRP, ESR), previous biological treatments; concomitant treatment (csDMARD/glucocorticoids (GC)). Serum Ig levels before every RTX cycle, the number of RTX cycles and adverse events (AE), including serious and opportunistic infections were also analysed. Results: We included 53 patients (86.8% women, mean age 55.5±13.5 years), 58% with a Charlson score ≥3. Mean disease duration was 16±9.1 years; 84.9% and 92.5% were RF and ACPA positive, respectively. Before starting RTX, 81% of patients had received other biologic drugs (58.5%≥2), 88% received concomitant csDMARD, (52% methotrexate and 32% leflunomide) and 81% were treated with GC (median dose 10 mg, P25–75 5–10 mg). The median number of RTX cycles received per patient was 5 (P25–75 2–6). 80 AE were reported: 12 infusion reactions, 8 cases of neutropenia, 51 infections (18 respiratory, 8 urinary, 4 skin and soft tissues, 8 gastrointestinal, 4 cases of non-disseminated herpes zoster, 1 bacteremia, 2 septic shock and 6 other) of which 19 were serious. and 5 malignancies (2 melanomas, 2 cervix, and 1 bladder) were also notified. No opportunistic infections were reported. Ig levels were obtained for 41 subjects: 7, 5 and 1 patients had low levels of IgG, IgM and IgA, respectively. Patients who developed infections received a greater number of RTX cycles (p<0.0002) and had more frequently low levels of serum IgG during follow-up (p<0.044) than those who did not have infections. Conclusions: Long-term exposure to RTX showed a good safety profile with a low incidence of serious infectious and no opportunistic infections. Factors associated with the development of infections were the number of cycles received and low serum levels of IgG at any point during follow-up. Acknowledgements: The authors would like to thank Dr. García de Yébenes who provided statistical support Disclosure of Interest: None declared